Outcomes of programmed death protein-1 inhibitors treatment of chronic active Epstein Barr virus infection: A single center retrospective analysis - Ma, Yaxian; Zhang, Peiling; Bao, Yuhan; Luo, Hui; Wang, Jiachen; Huang, Liang; Zheng, Miao (Frontiers in Immunology, 2023)
Chronic active Epstein-Barr virus (CAEBV) disease is a high-mortality disease, which is characterized by persistent infectious mononucleosis-like symptoms. There is no standard treatment for CAEBV and allogeneic hematopoietic stem cell transplantation (HSCT) was considered the only potentially therapeutic approach. PD-1 inhibitors have achieved high response in many Epstein-Barr virus-related diseases. In this single-center retrospective analysis, we report the outcomes of PD-1 inhibitors treatment of CAEBV. All CAEBV patients without hemophagocytic lymphohistiocytosis (HLH), who were treated with PD-1 inhibitors in our center between 6/1/2017 and 12/31/2021, were retrospectively analyzed. The efficacy and safety of the PD-1 inhibitors were evaluated. Among the sixteen patients with a median age at onset of 33 years (range, 11-67 years), twelve patients responded to PD-1 inhibitors and the median progression-free survival (PFS) was 11.1 months (range, 4.9-54.8 months). Three achieved clinical complete response (clinical CR), as well as molecular CR. Five patients achieved and remained partial response (PR), and four converted from PR to no response (NR). For three CR patients, the median time and cycles from the first application of PD-1 inhibitor to clinical CR were 6 weeks (range, 4-10 weeks) and 3 cycles (range, 2-4 cycles), and molecular CR was achieved after a median of 16.7 weeks (range, 6.1-18.4 weeks) and 5 cycles (range, 3-6 cycles) of PD-1 inhibitor infusion. No immune-related adverse events have been observed except for one patient who suffered immune-related pancreatitis. There was no correlation of treatment outcome with blood count, liver function, LDH, cytokine or ferritin levels. NK cell function, PD-L1 expression in tumor tissue and gene mutation possibly correlated with treatment response. In patients with CAEBV, PD-1 inhibitors have tolerable toxicity and comparable outcomes while improving quality of life and financial toxicity. Larger prospective studies and longer follow-up time is needed to be conducted.